%! TEX root = Galois.tex % vim: tw=50 % 21/10/2023 12AM \begin{remark*} \glsadjdefn{hom_poly}{homogeneous}{polynomial} We can write any $f \in \radj R[X_1, \ldots, X_n]$ as $f = \sum_d f_d$ where $f_d$ is \emph{homogeneous} of degree $d$ (i.e. each monomial has total degree $d$). Clearly $f$ \gls{symmetric} implies all $f_d$ are \gls{symmetric}. So for the proof of \nameref{symm_func_thm}(i), it suffices to consider $f \in \radj R[X_1, \ldots, X_n]$ which is \gls{symmetric} and homogeneous of degree $d$. \end{remark*} \begin{flashcard}[lexicographic-ordering-defn] \begin{definition*}[lexicocraphic ordering] \glsnoundefn{lex_ord}{lexicographic ordering}{N/A} \cloze{ Define the \emph{lexicographic ordering} of monomials such that \[ X_1^{i_1} X_2^{i_2} \cdots X_n^{i_n} > X_1^{k_1} X^{j_2} \cdots X_n^{j_n} \] if $i_1 = j_1, i_2 = j_2, \ldots, i_{r - 1} = j_{r - 1}, i_r > j_r$ for some $1 \le r \le n$. This is a total ordering. } \end{definition*} \end{flashcard} \begin{flashcard}[symm-func-thm-proof] \prompt{Proof of \nameref{symm_func_thm}?} \begin{proof}[Proof of \nameref{symm_func_thm}] \phantom{} \begin{enumerate}[(i)] \item \cloze{ By previous remark, we may split $f$ into a sum of homogeneous polynomials, and just prove that each term in the sum can be written as a sum of \gls{elem_symm_func}. Let $X_1^{i_1} X_2^{i_2} \cdots X_n^{i_n}$ be the largest monomial (with respect to \gls{lex_ord}) to appear in $f$ with non-zero coefficient ($c$ say). Since $X_{\sigma(1)}^{i_1} X_{\sigma(2)}^{i_2} \cdots X_{\sigma(n)}^{i_n}$ also appears in $f$ for all $\sigma \in S_n$, we must have $i_1 \ge i_2 \ge i_3 \ge \cdots i_n$. Write \[ X_1^{i_1} X_2^{i_2} \cdots X_n^{i_n} = X_1^{i_1 - i_2} (X_1 X_2)^{i_2 - i_3} \cdots (X_1 X_2 \cdots X_n)^{i_{n - 1} - i_n} \] Let $g = \symmpoly_1^{i_1 - i_2} \symmpoly_2^{i_2 - i_3} \cdots \symmpoly_n^{i_n}$. Then $f$ and $g$ are both \gls{hom_poly} of degree $d$ and have the same \glsref[lex_ord]{largest} monomial. So $f - cg$ is either $0$, or it is a \gls{symm_poly} of degree $d$, whose leading monomial is \glsref[lex_ord]{smaller} than that of $f$. Since there are only finitely many monomials of degree $d$ in $\radj R[X_1, \ldots, X_n]$, the process stops after finitely many steps. Therefore we can write $f$ as a polynomial in $\symmpoly_1, \ldots, \symmpoly_n$. } \item \cloze{Write $\symmpoly_{r, n}$ instead of $s_r$ to indicate the number of variables involved. Suppose $G \in \radj R[Y_1, \ldots, Y_n]$ with $G(\symmpoly_{1, n}, \symmpoly_{2, n}, \ldots, \symmpoly_{n, n}) = 0$. We must prove that $G = 0$. The proof is by induction on $n$. The case $n = 1$ is clear. Write $G = Y_n^k H$ with $Y_n \nmid H$, $k \ge 0$. Since $\symmpoly_{n, n} = X_1 X_2 \cdots X_n$, it is not a zero divisor in $\radj R[X_1, \ldots, X_n]$, so we have \[ H(\symmpoly_{1, n}, \symmpoly_{2, n}, \ldots, \symmpoly_{n, n}) = 0 \] So we may assume that $G$, if non-zero, is not divisible by $Y_n$. Replacing $X_n$ by $0$ gives \[ \symmpoly_{r, n} (X_1, \ldots, X_{n - 1}, 0) = \begin{cases} \symmpoly_{r, n - 1}(X_1, \ldots, X_{n - 1}) & r < n \\ 0 & r = n \end{cases} \] Therefore \[ G(\symmpoly_{1, n - 1}, \symmpoly_{2, n - 1}, \ldots, \symmpoly_{n - 1, n - 1}, 0) = 0 \] By induction hypothesis, $G(Y_1, \ldots, Y_{n - 1}, 0) = 0$, hence $Y_n \mid G$. So by the above $G$ must be zero.} \qedhere \end{enumerate} \end{proof} \end{flashcard} \begin{example} Let $f = \sum_{i \neq j} X_i^2 X_j$. The leading term (in \gls{lex_ord}) is $X_1^2 X_2 = X_1(X_1 X_2)$. Calculate: \begin{align*} \symmpoly_1 \symmpoly_2 &= \sum_i \sum_{j < k} X_i X_j X_k \\ &= \ub{\sum_{i \neq j} X_i^2 X_j}_{=f} + 3 \sum_{i < j < k} X_i X_j X_k \end{align*} So $f = \symmpoly_1 \symmpoly_2 - 3 \symmpoly_3$. \end{example} \begin{flashcard}[] \begin{example} \glsnoundefn{disc_f}{discriminant}{discriminants} \glssymboldefn{disc_f}{Disc}{Disc} Let $f(X) = \prod_{i = 1}^n (X - \alpha_i)$ be a monis polynomial with roots $\alpha_1, \ldots, \alpha_n$. The \emph{discriminant of $f$} is \[ \Disc(f) = \cloze{\prod_{i < j} (\alpha_i - \alpha_j)^2} \] \cloze{By the \nameref{symm_func_thm}, we can write $\Disc(f)$ as a polynomial in the coefficients of $f$.} \fcscrap{ $n = 2$, $f(X) = X^2 + bX + c = (X - \alpha_1)(X - \alpha_2)$. Then \begin{align*} \Disc(f) &= (\alpha_1 - \alpha_2)^2 \\ &= (\alpha_1 + \alpha_2)^2 - 4\alpha_1 \alpha_2 \\ &= b^2 - 4ac \end{align*} It is clear from the definition that \[ \Disc(f) = 0 \iff \text{$f$ has repeated roots} \] } \end{example} \end{flashcard} \newpage \section{Normal and separable extensions} \begin{flashcard}[normal-extension-defn] \begin{definition*}[normal extension] \glsadjdefn{norm_ex}{normal}{extension} \cloze{ An \gls{ex} $L \extendover K$ is \emph{normal} if it is \gls{alg_ex} and the \gls{min_poly} of every $\alpha \in L$ splits into linear factors over $L$. Equivalently if $f \in \radj K[X]$ is irreducible and has a root in $L$, then it splits into linear factors over $L$. \fcscrap{(slogan: ``one out -- all out'').} } \end{definition*} \end{flashcard} \begin{flashcard}[splitting-fields-are-normal-thm] \begin{theorem}[Splitting fields are normal] \cloze{Let $\exdeg [L : K] < \infty$. Then \[ \text{$L \extendover K$ is \gls{norm_ex}} \iff \text{$L$ is a \gls{splitting_field} for some $f \in \radj K[X]$} \] } \end{theorem} \begin{proof} \phantom{} \begin{enumerate}[$\Rightarrow$] \item[$\Rightarrow$] \cloze{Write $L = \fadj K(\alpha_1, \ldots, \alpha_n)$. Let $f_i$ be the \gls{min_poly} of $\alpha_i$ over $K$. Then \begin{align*} \text{$L \extendover K$ \gls{norm_ex}} &\implies \text{$f_i$ splits into linear factors over $L$} \\ &\implies \text{$L$ is a \gls{splitting_field} for $\prod_i f_i$} \end{align*} } \item \cloze{Let $L$ be the \gls{splitting_field} of $f \in \radj K[X]$ over $K$. Let $\alpha \in L$ have \gls{min_poly} $g$ over $K$. Let $M \extendover L$ be a \gls{splitting_field} for $g$. We must show that whenever $\beta$ is a root of $g$ then in fact $\beta \in L$. Then $L = \fadj L(\alpha)$ is a \gls{splitting_field} for $f$ over $\fadj K(\alpha)$, and $\fadj L(\beta)$ is a \gls{splitting_field} for $f$ over $\fadj K(\beta)$. $\alpha$ and $\beta$ have the same \gls{min_poly} $g$ over $K$, so $\fadj K(\alpha)$ and $\fadj K(\beta)$ are \Kisomic{K}. By \nameref{uniqueness_of_splitting_fields}, $\fadj L(\alpha)$ and $\fadj L(\beta)$ are \Kisomic{K}. Therefore $\exdeg[L : K] = \exdeg[\fadj L(\beta) : K]$. So by \nameref{tower_law}, $[\fadj L(\beta) : L] = 1$, so $\fadj L(\beta) = L$, so $\beta \in L$. }\qedhere \end{enumerate} \end{proof} \end{flashcard}